GROUP DECISION SUPPORT SYSTEM UNTUK MENENTUKAN KENAIKAN JABATAN MENERAPKAN METODE GAP PROFILE MATCHING - Hendra Prayitno; Diana Diana (Direktorat Riset dan Pengabdian Pada Masyarakat (DRPM) Universitas Bina Darma, 2021)
The aims of this study is to build a Group Decision Support System (GDSS) application to determine employee promotions. There are three assessment teams in this GDSS, namely the general manager, HRD 1 and HRD 2. This is expected to reduce subjectivity in determining employee promotions. There are two criteria used, namely work attitude and intellectual capacity. Each criterion has several sub-criteria. The work attitude criteria consist of 8 sub-criteria, namely appearance, discipline, ability to accept opinions, motivation, self-confidence, courtesy, responsibility and honesty. Intellectual capacity criteria consist of 4 sub-criteria, namely knowledge insight, communication, speed of thinking and loyalty. The application of the GAP Profile Matching method has been proven to improve the performance of the GDSS. This method is recommended as one of the appropriate methods to select employees who have the most appropriate profile with the job profile. In this method, the smaller the GAP between the employee profile, the greater the opportunity for the employee to be able to occupy the position offered.